HUBUNGAN ANTARA TINGKAT PENGETAHUAN DAN SIKAP TERHADAP KEPATUHAN UNTUK MELAKSANAKAN PHYSICAL DISTANCING DALAM MEMUTUS RANTAI PENYEBARAN COVID-19 - Reza Mardiana Ayu Oktavia; Eva Pravitasari Nefertiti; Lestari Dewi; Annisa Ullya Rasyida (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
COVID-19 is a severe pandemic outbreak caused by SARS CoV-2 in China on December 2019, it has spread to various countries very quickly. The preventive spread of the virus is applied to physical distancing. This study aims to analyze the correlation between the level of knowledge and attitude towards behavior to carry out physical distancing to breaking the spread of COVID-19 to 7th-semester students of the Faculty of Medicine, Hang Tuah University, Surabaya. Analytic observational method with a quantitative approach to cross-sectional study design. A total of 67 samples using the simple random sampling method. The information has been collected online on November 2020 in 7th-semester students of the Faculty of Medicine, Hang Tuah University, Surabaya. The Results Spearman's correlation test analysis showed that the p-value=0.604 (> 0.05) for the knowledge and behavior variables, while the p-value = 0.385 (> 0.05) for the attitude and behavior variables, so HO accepted. The correlation value is 0.064 for the knowledge and behavior variables, while the correlation value is 0.108 for the attitude and behavior variables. Both indicated “very weak” strength and positive direction of correlation. The conclusion of this study is uncorrelation between the level of knowledge and attitude towards behavior to carry out physical distancing to breaking the spread of COVID-19 to 7th-semester students of the Faculty of Medicine, Hang Tuah University, Surabaya.